MORPHOLOGICAL AND HISTOLOGICAL ALTERATIONS OF THE GASTRIC MUCOSA INDUCED BY EXPERIMENTAL ACUTE STRESS IN ANIMAL MODELS - Adxamjanova S.S; Mirsharapov Utkir Mirsharapovich; Akhmedova Sayyora Mukhamadovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study investigates the profound morphological and histological changes in the gastric mucosa triggered by experimental acute stress. While the physiological responses to stress are well-documented, the precise microstructural alterations in the stomach require continuous exploration to develop targeted cytoprotective therapies. Using a Water Immersion Restraint Stress (WIRS) model on Wistar rats, we analyzed the gastric tissue through histological and morphometric techniques. The findings reveal significant mucosal degradation, including severe hyperemia, microvascular thrombosis, epithelial desquamation, and hemorrhagic erosions in the stress-subjected group compared to the control. The study underscores the critical role of ischemia and compromised mucosal microcirculation in the pathogenesis of stress-induced gastric lesions, emphasizing the need for prophylactic pharmacological interventions.